Servant leadership, psychological safety, psychological capital, regulatory focus, and turnover intention among nurses in Pakistan - Brohi, Noor Ahmed (2019)
The importance of attracting and retaining professional employees is undisputed with researchers as well as practitioners. From a managerial perspective, the attraction and retention of high-quality professional employees are more important today than ever before because of a few trends (e.g., globalization, increase in knowledge work, and accelerating rate of technological advancement) which make it vital that firms acquire and retain the best human capital. In the 21st century, research on employee turnover and retention continue to hold widespread and global attention. The global shortage of skilled workforce is prevailing in an Asian country like Pakistan which is also facing serious issues related to workforce shortage. This issue existed in the healthcare sector as well which is considered as one of the important sectors in any country. Furthermore, within the healthcare sector, nurses play an essential role because of their job description which brings them in direct contact of patients and caretaker of the patients care at healthcare sector. Pakistani Healthcare sector is facing serious issues of turnover which results in acute shortage of skilled nurses. In a sample of 374 nurses working in public hospital using Smart-PLS technique to test the proposed hypotheses, this study investigated the key characteristics of servant leadership style as penned by Robert Greenleaf that servant leaders guide followers to adopt the behaviour of their leaders by putting others need above their own. In this study, author developed and tested a model contending that servant leaders increase employees’ psychological safety that organization is a safe place to speak up ideas, opinions and take decisions, and psychological capital that employees value resources and keep the resources, which directly influences nurse’s turnover intention. As hypothesized, servant leadership was negatively related with nurse’s turnover intention and positively related to psychological safety and psychological capital. Psychological safety and psychological capital mediated the relationship between servant leadership and turnover intention. Further, this study posits that the relationship between servant leadership, psychological safety, psychological capital, and turnover intention is conditional to the dispositional factors, i.e. employees regulatory focus. The components of regulatory focus, promotion focus moderated the indirect relationship between servant leadership and turnover intention through psychological safety and psychological capital. Whereas, prevention focus was significant between the indirect effect of psychological safety but was not significant between the indirect effect of psychological capital.